(untitled) (Bangladesh Medical Journal, 2012)
Despite supplementation of iron folic acid tablets over the past few decades, no marked improvement has been noticed in the magnitude of anemia in Bangladesh. It has been a felt need to have a fresh look at the problem of iron/folic acid deficiency anemia prevailing in Bangladesh and the perspective of the supplementation program. Data were collected through a review of a good number of available documents and in-depth interviews of concerned policy makers, stakeholders and care providers. An iron folic acid supplementation component is formally in place in the Health, Nutrition, and Population Sector Program (HNPSP) and implemented by both the health and family planning wings of the Ministry of Health and Family Welfare (MoHFW). The iron folic acid component primarily focuses on the pregnant and lactating women and fails to focus other groups who also are equally affected. Tablets are provided on a weekly basis, thus not completing the required dose. A holistic approach is required to combat this long standing problem. DOI: http://dx.doi.org/10.3329/bmj.v39i3.9952 BMJ 2010; 39(3)